Leveraging Clinical Decision Support in Dental Settings to Bridge HIV Testing Gaps and Contribute to Ending the Epidemic - Perelman, Sharon C.; Ansari, Tunaidi; Yin, Michael T.; Gordon, Peter G.; Nguyen, Nadia; Evangelidis-Sakellson, Vicky; Kunzel, Carol; Meyers, Kathrine; Castor, Delivette; Blanchard, Ariel; Albert, David A. (ACI Open, 2025)
Background Columbia University Irving Medical Center (CUIMC) in New York City, in collaboration with the Division of Infectious Diseases and the Dental School, is addressing a critical gap in HIV testing to support the strategy to End the HIV Epidemic (EHE). This strategy emphasizes increasing testing rates and providing patients with information about pre-exposure prophylaxis (PrEP).Objectives This study aimed to achieve two key objectives: (1) develop a robust clinical decision support system (CDSS) capable of identifying patients who stand to benefit from HIV testing and (2) implement a seamlessly integrated, user-friendly workflow, enabling health care providers to effortlessly order and conduct HIV point-of-care (POC) screening.Methods A targeted CDSS was developed by identifying a patient population, determining qualifying laboratory tests, interpreting HIV and sexually transmitted infections results, and programming based on conditional statements. A workflow was implemented after careful consideration and collaboration with faculty and residents. POC testing was conducted using the OraQuick Rapid Antibody Test Advanced HIV-1/2.Results The implementation of this targeted CDSS and associated new protocols demonstrated a promising 11.5% testing rate, normalizing HIV POC testing within the dental ambulatory care setting, and representing a key pillar of EHE.Conclusion CUIMC's approach presents a promising strategy for bridging gaps in HIV testing disparities and enhancing public health outcomes. By leveraging CDSS and innovative health care delivery methods, CUIMC's desire is to expand the scope and effectiveness of HIV testing to other practices and sites.
Keywords: electronic health records and systems; clinical decision support systems; human immunodeficiency virus; point-of-care diagnostic testing; dental clinic